مشكلة التفضيل النقدي ونقص السيولة المحلية بالمصارف الليبية - يونس علي أسعيد البرغثي (Scientific Journal of University of Benghazi, 2018)
The Libyan economy like most developing economics which characterized by an underdeveloped monetary system, is suffering from a problem of cash preference, where traders in the market prefer dealing with the legal money rather than dealing with deposit money. Lately, the problem has intensified as the Libyan banks, became incapable of fulfilling the daily withdrawal demands from deposits. Even though its retention of reserve and liquidity is surplus. This research aims to identify the main reasons of this problem and its economic and social impacts. In addition to figure some suggestions help solving such a problem. The outcome of the study reached a number of results, the most important of which is the impact of these fluctuations on the economic, political and security factors on the volatility of the values of the coefficient of monetary preference. In turn this reflects the impact of these factors on the increasing demand for the currency, and that the problem of monetary preference may turn into a problem of lack of liquidity, when the economic crisis is linked to other political and security crises.